Inconsistency of Sentinel Events and No Gender Difference in the Measurement of Work-Related Stress. (15th February 2016) - Andrisano-Ruggieri, Ruggero; Capunzo, Mario; Crescenzo, Pietro; Savastano, Riccardo; Truda, Giovanna; De Caro, Francesco; Pennisi, Manuela; Boccia, Giovanni
Usually, sentinel events and gender are useful variables to propose appropriate intervention strategies for promoting public health. The Italian legislation has incorporated aspects of the scientific literature of stress into law 81/08 and the ministerial circular of November 18, 2010, obliging the detection of work-related stress with specific reference to gender and working environment characteristics. Specifically, the Italian law requires the discovery of sentinel events in the working environment. This study evaluates the role of sentinel events in the detection of work-related stress in relation to gender. The sample includes 249 Italian subjects of a debt collection company divided into two groups (male and female) and distributed in two different categories: Inside Sentinel Events and Outside Sentinel Events. A multifactorial questionnaire, the Organizational and Psychosocial Risk Assessment (OPRA), was administered. The application of two-way ANOVA did not show any statistically significant differences due to gender between the subjects who belonged to the sentinel events group and those who did not belong, as assessed by the Risk Index, the Inventory of Source of Risk, and variables linked to work conditions (work function and seniority). Significant differences were found between men and women only on the index of physical and mental health. Subsequently, three performed linear regression confirm the same results.